THE PRINCIPLE OF RECORDING INFORMATION IN DISTRIBUTED ENVIRONMENTS VIA SULEIMENOV-MUN’S WAVES - M., Dolayev; P., Obukhova; S., Panchenko; R.B., Bakytbekov; R.S., Ivlyev; K., Chezhimbayeva (European Scientific Journal, ESJ, 2013)
A new approach to information recording in distributed media based on the forced wave excitation involved by temperature fluctuations was proposed. The scheme of the device providing the implementation of the proposed approach is considered.